Anesthetic considerations for stereotactic electroencephalography implantation - Chakrabarti Rajkalyan; Anurag Tewari; Shilpa Rao; Rafi Avitsian (Wolters Kluwer Medknow Publications, 2019)
The refractory seizures have significant impact on the quality of life and increase long term neurologic and non-neurologic complications. Implantation of Stereotactic Electroencephalography (SEEG) leads is one of the newer surgical techniques intended to localize seizure foci with higher accuracy than the conventional methods. Most of the commonly utilized anesthetic agents depress EEG waveforms affecting intra operative monitoring during these surgeries. Hence, the anesthetic goals include a stable induction and maintenance with agents which have minimal effect on EEG. This article discusses the peri-operative considerations of multiple anti-epileptic medications, recent advances in anesthetic management, and important post-operative concerns.